2014
DOI: 10.3102/0162373714533817
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Effects of No Child Left Behind on Teachers’ Work Environments and Job Attitudes

Abstract: Ten years into the implementation of No Child Left Behind (NCLB), a growing body of research seeks to assess the law's impact on American public schools. Much of this work rightly focuses on effects on students, with evidence suggesting that NCLB has resulted in small but positive effects on student achievement, particularly in math (e.g., Ballou & Springer, 2011;Dee & Jacob, 2011). Although research into the mediating factors driving this achievement growth is nascent, it is unlikely that NCLB could affect st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 50 publications
1
45
0
1
Order By: Relevance
“…In understanding the potential implications for other regions in the United States, one must proceed with some caution. While NCLB has affected all states, consequences have been felt differently depending on whether NCLB presented new accountability reforms (Grissom, Nicholson-Crotty, and Harrington 2014;Reback, Rockoff, and Schwartz 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In understanding the potential implications for other regions in the United States, one must proceed with some caution. While NCLB has affected all states, consequences have been felt differently depending on whether NCLB presented new accountability reforms (Grissom, Nicholson-Crotty, and Harrington 2014;Reback, Rockoff, and Schwartz 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The similarity of the SASS to variables investigated in CARD research allowed us to replicate of the classification strategy used to place teachers in the three Appraisal groups: Demands, Balanced, and Resourced. Both the 1999-2000 and 2007-2008 SASS surveys 1 were used in this study because there is some evidence that increased high-stakes testing and accountability brought on by No Child Left Behind (NCLB) has led to increased stressors and demands on many teachers (Berryhill, Linney, & Fromewick, 2009;Grissom, Nicholson-Crotty, & Harrington, 2014). Utilizing the 2000 and 2008 surveys provided information about teachers' perceptions of classrooms, both before and after implementation of the No Child Left Behind Act.…”
Section: Background Examining Teacher Perceptions Using the Transactimentioning
confidence: 99%
“…Surprisingly, however, we found scant research using the SASS to evaluate the role of stress in teacher dissatisfaction or intention to leave the field. Grissom et al (2014) used the SASS data to investigate teacher work environments across several administrations of the SASS and defined teacher demands as the number of hours in the week teachers spend working and support from the school, but did examine teacher resources. Interestingly, they found that while teachers' reported weekly work increased 2 hours between 2000 and 2004 (just before No Child Left Behind was enacted), work hours leveled off between 2004 and 2008.…”
Section: Teacher Vocational Concernsmentioning
confidence: 99%
“…Ironically, after years of research establishing a decades‐long decline in the academic aptitude of new teacher hires (Corcoran, Evans, and Schwab , ; Hoxby and Leigh ), a study by Goldhaber and Walch () estimated a slight turnaround in this pattern of declining aptitude noting that there have been small improvements in the academic ability of new teacher hires in the United States precisely during the time in which state and local governments have been ratcheting up these aforementioned performance management reforms. Although their observation is not causal, the correlation warrants more research into the ways in which accountability and evaluation reforms influence the quality of employees sorting across government agencies (e.g., school districts) and into government work itself (see also Grissom, Nicholson‐Crotty, and Harrington for a good example of research investigating the effect of performance management reforms on teacher job satisfaction and commitment).…”
Section: Resultsmentioning
confidence: 99%